2020
DOI: 10.1155/2020/4892382
|View full text |Cite
|
Sign up to set email alerts
|

Suggestions for Radiation Oncologists during the COVID‐19 Pandemic

Abstract: SARS-CoV-2 pandemic and COVID-19 diffusion have recently become an international public health emergency. Cancer patients, as a frail population, are particularly exposed to the risk related to infections. The clinical decision-making process and the organizational workflow of radiotherapy department should be revised in the light of the critical situation. We herein provide practical suggestions derived from the available literature and discussed during an online session held within the e-learning educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…However, when, WBI is required, one of the 5 fraction schedules (28–30 Gy in once weekly fractions, or 26 Gy in 5 daily fractions) can be chosen. Boost dose to the tumor bed should be omitted in patients >40 years and/or with low-risk factors for LR [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when, WBI is required, one of the 5 fraction schedules (28–30 Gy in once weekly fractions, or 26 Gy in 5 daily fractions) can be chosen. Boost dose to the tumor bed should be omitted in patients >40 years and/or with low-risk factors for LR [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, when, WBI is required, one of the 5 fraction schedules (28-30 Gy in once weekly fractions, or 26 Gy in 5 daily fractions) can be chosen. Boost dose to the tumor bed should be omitted in patients >40 years and/or with low-risk factors for LR [24]. Curigliano et al [25] recommended evaluating RT omission in the light of the local situation, but to reconsider this indication for the individual patient every four weeks.…”
Section: Recommendations During Covid 19 Pandemicmentioning
confidence: 99%
“…COVID-19 pandemic has resulted in considerable overloading of health care systems in almost all regions of the world. Previous reports have shown that, compared to the normal population, patients with cancer are more prone to develop COVID-19 complications and death as these frail populations have a higher risk of developing severe respiratory manifestations and requiring invasive ventilation (1).…”
Section: Contextmentioning
confidence: 99%
“…In this publication the author searched for multidisciplinary and expert recommendations to guide potential shift in RT indications and found limited data as of April 2020 when it was published however provides a good summary of the available data at that point. Chen et al and Franco et al provide broader frameworks for prioritization of patients [6,18]. Franco et al also provides guidelines for the management of patients with COVID-19 [18].…”
Section: Indications For/modification Of Rt -Modify Rt When Possible mentioning
confidence: 99%
“…Chen et al and Franco et al provide broader frameworks for prioritization of patients [6,18]. Franco et al also provides guidelines for the management of patients with COVID-19 [18].…”
Section: Indications For/modification Of Rt -Modify Rt When Possible mentioning
confidence: 99%